Immuno-inflammatory activation in acute cardio-embolic strokes in comparison with other subtypes of ischaemic stroke - Licata, Giuseppe; Tuttolomondo, Antonino; Raimondo, Domenico Di; Corrao, Salvatore; Sciacca, Riccardo Di; Pinto, Antonio (Thrombosis and Haemostasis, 2009)
Few studies have examined the relationship between inflammatory biomarker blood levels, cardioembolic stroke subtype and neurological deficit. So the aim of our study is to evaluate plasma levels of immuno-inflammatory variables in patients with cardio-embolic acute ischaemic stroke compared to other diagnostic subtypes and to evaluate the relationship between immuno-inflammatory variables, acute neurological deficit and brain infarct volume. One hundred twenty patients with acute ischaemic stroke and 123 controls without a diagnosis of acute ischaemic stroke were evaluated. The type of acute ischaemic stroke was classified according to the TOAST classification. We evaluated plasma levels of IL-1β, TNF-α, IL-6 and IL-10, E-selectin, P-selectin, sICAM-1,sVCAM-1, vWF, TPA and PAI-1. Patients with ischaemic stroke classified as cardio-embolic (CEI) showed, compared to other subtypes, significantly higher median plasma levels of TNF-α , IL-6 and IL-1β. Furthermore stroke patients classified as lacunar showed, compared to other subtypes, significantly lower median plasma levels of TNF-α, IL-6 and IL-1β. Multiple linear regression showed a significant association between the Scandinavian Stroke Scale (SSS) score at admission and diagnostic subtype, infarct volume of cardio-embolic strokes and some inflammatory variables. Our findings confirm that cardio-embolic strokes have a worse clinical presentation and produce larger and more disabling strokes than other ischaemic stroke subtypes reporting a possible explanation of higher immuno-inflammatory activation of the acute phase.
Keywords: Cerebral infarct; cerebrovascular accident; cerebrovascular disease; inflammation; risk factors; stroke; cytokines